2016
DOI: 10.4037/ajcc2016215
|View full text |Cite
|
Sign up to set email alerts
|

Functional Status and Disability in Patients After Acute Stroke: A Longitudinal Study

Abstract: Background Stroke is a major public health problem. Objective To use the Barthel Index to evaluate basic activities of daily living in stroke survivors and detect any predictors of functional outcome at 6 months after stroke. Methods In an observational longitudinal study, data were gathered on consecutive patients admitted to the comprehensive stroke unit at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
30
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 36 publications
(48 reference statements)
5
30
0
3
Order By: Relevance
“…Characteristics of the hospital-based cohort studies are summarized in online supplemental Table 3. Among the 12 studies, 11 studies were prospective cohorts recruited during hospitalization [25,[39][40][41][42][43][44][45][46][47][48]. There was 1 US [39] and 1 Asian cohort [25], while the majority of cohorts were from European countries [40][41][42][43][44][45][46][47][48][49].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Characteristics of the hospital-based cohort studies are summarized in online supplemental Table 3. Among the 12 studies, 11 studies were prospective cohorts recruited during hospitalization [25,[39][40][41][42][43][44][45][46][47][48]. There was 1 US [39] and 1 Asian cohort [25], while the majority of cohorts were from European countries [40][41][42][43][44][45][46][47][48][49].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…One study was conducted in veterans [39]. In the majority of the studies, the mean/median age of the participants was between 70 and 75 years old [40][41][42][43][44][45][46][47][48].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Stroke is the second most common cause of mortality worldwide [1,2], and it is the third leading cause of adult disability [3]. Indeed, approximately 90 % of stroke survivors are left with some residual deficits.…”
Section: Introductionmentioning
confidence: 99%
“…In the Netherlands, van den BosGA et al examined a small sample of stroke patients (n = 465) and found that there was no significant association of low level of education with disability (Barthel Index and mRS) at 6 months and 5 years post-stroke [15]. A study of small sample (n = 175) in Spain reported that socioeconomic level did not affect patients' functional recovery in 6 months after stroke [16]. In Europe, Putman et al analyzed the data of 419 consecutive patients with stroke and got conflicting results: during inpatient stay, functional impairment 6 months after stroke was associated with a low educational level but not low income, and between discharge and 6 months post stroke, no significant association was found with the educational level and income [17].…”
Section: Discussionmentioning
confidence: 99%